Nurse’s experience in nursing children with cancer - Juozapavičienė, Rasa; Bakanaitė, Salomėja; Balčiūnienė, Regina (Slauga. Mokslas ir praktika, 2020)
Communication is the most important connection way of communication between the nurse and the patient. Proper and effective communication is becoming more and more relevant as it improves the relationship between nurse and patient, influences the patient’s perception of the quality of healthcare and the outcome of treatment. Care for children with oncological diseases is a highly skilled job. The nurse must have some knowledge and experience to fulfill the needs of the patient and provide quality care. Today oncological diseases in children have been and remain an important and relevant public health issue not only in Lithuania, but in all countries of the world. The nurse provides the greatest and most valuable support in communicating on children with oncological diseases. Therefore, it is very important to analyze the importance of communication and problems related with nursing experiences in caring for children with this disease. Purpose of the study - to reveal the nurse’s communication experience in caring for children with oncological diseases. Contingency of the study. A total of 10 nurses aged between 25 and 50 years working with children with oncological diseases. Research methods. The study was conducted in a semi-structured interview with patients with oncological diseases. Research data is analyzed using the content analysis method. Results: A particular environment can improve or worsen communication. Research data shows that nurses choose different communication spaces for the conversation, while communicating with children with oncological diseases, depending on the age of the child. Analyzing the interview material, emerged that nursing communication on child with oncologic disease is affected by various environmental, political / economic, social / cultural and psychological factors. Nurses say that it is important for the child to choose a ward, a space for communication, to use as little medical terms as possible, to talk to the child in a language that is understandable, to take into account the child’s existing mood and fears, to notice the emotional state of the relatives when they are tired or exhausted. The study revealed that nurses are not always aware of what parents or children have to answer for straightforward, disease-related questions about how to properly choose words. According to the survey, nurses feel bad when they hear the different, incorrect comments from patients and their relatives towards them. The study revealed that the persistent physical, psychological and social difficulties are felt in dealing with an oncologic child cause a variety of health problems for the nurse. Conclusions: Nurses face psychological, physical and social difficulties when communicating with children with oncological diseases. They experience depression, sadness, a desire to disengage from the patient, feel inner pain, increased sensitivity, stress, anxiety, fatigue, insomnia, lack of psychological knowledge, inadequate patient evaluation as a nurse care specialist. When dealing with communication difficulties, caregivers look for solutions with the child, leave it for reflection, engage in acceptable activities, apply to the child’s family members / loved ones, to another departmental physician, psychologist or senior nurse.